Du grenier au marché - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Les greniers Par M Hoogland & P Holen. Agromisa - CTA, Agrodok N° 25. 2001. 86 pages.